Flow in the Nose region of a Taylor Bubble Rising through Vertical Columns of Liquids - Sofia Nogueira (2004)
The flow in the nose region and in the annular film around individual Taylor bubbles rising through stagnant and co-current vertical columns of liquid were studied, employing particle image velocimetry (PIV) and pulsed shadowgraphy techniques (PST) at the same time. The combined techniques enabled simultaneous determination of the bubble shape and the velocity profiles in the liquid film. Experiments were performed with water and aqueous glycerol solutions in a wide range of viscosities (1 × 10−3 Pa s < < 1.5 Pa s), in an acrylic column of 32 mm ID. Values for the distance ahead of the nose in which the flow is disturbed by the presence of the bubble are presented for the conditions studied. The bubble shapes in the nose region are compared with Dumitrescu's shape for potential flow. The velocity profiles show that after the nose region the liquid begins to accelerate downwards, and at a certain distance from the bubble nose the velocity profile and the liquid film thickness stabilise. The liquid film acquires characteristics of a free-falling film. Values of the developing length and film thickness are reported for the experimental conditions studied. Average velocity profiles in the fully developed film are also presented. A critical Reynolds number of around 80 (based on the mean absolute velocity in the liquid film and on the film thickness) is reported for the transition from laminar to turbulent regime. Shear stress profiles (in the fully developed film) are also provided. The data reported are relevant for the validation of numerical codes in slug flow. 2005 Elsevier Ltd. All rights reserved.